Citral presents cytotoxic and genotoxic effects in human cultured cells - Souza, Ana C. S. [UNESP]; Silva, Laís K. [UNESP]; Queiroz, Thais B. [UNESP]; Marques, Eduardo S. [UNESP]; Hiruma-Lima, Clélia A. [UNESP]; Gaivão, Isabel O. M.; Maistro, Edson L. [UNESP] (Taylor & Francis, 2019)
Citral, 3,7-dimethyl-2,6-octadien-1-al, one of the main components of the essential oils obtained from several plants, is used as a food additive and as a fragrance for detergents, cosmetics and other toiletries. The literature shows disparity regarding citral genotoxicity. Thus, the main objective of our work was to evaluate the genotoxic effects of citral in human cell cultures, HepG2 and leukocytes. Cytotoxicity assays (trypan blue and MTT) showed citral toxic effects in HepG2 cells (with metabolizing liver enzymes), which contrasted with the absence of toxicity in leukocytes. After citral exposure, both cell types did not demonstrate clastogenic/aneugenic effects in the micronucleus test. However, for the comet assay, citral exposure lead to significant genotoxic effects in both HepG2 (even to citral low concentrations) and leukocytes. The use of citral must be viewed with caution due to its ability to induce DNA damages, especially after being metabolized by cells with active liver enzymes.
Keywords: 3,7-dimethyl-2,6 octadienal; comet assay; micronucleus test; MTT assay